Characterization of Patients With Lupus Nephritis Included in a Large Cohort From the Spanish Society of Rheumatology Registry of Patients With Systemic Lupus Erythematosus (RELESSER). Issue 9 (March 2016) - Galindo-Izquierdo, María; Rodriguez-Almaraz, Esther; Pego-Reigosa, José M.; López-Longo, Francisco J.; Calvo-Alén, Jaime; Olivé, Alejandro; Fernández-Nebro, Antonio; Martinez-Taboada, Víctor; Vela-Casasempere, Paloma; Freire, Mercedes; Narváez, Francisco J.; Rosas, José; et al.
Abstract : Abstract: The aim of the study was to profile those patients included in the RELESSER registry with histologically proven renal involvement in order to better understand the current state of lupus nephritis (LN) in Spain. RELESSER-TRANS is a multicenter cross-sectional registry with an analytical component. Information was collected from the medical records of patients with systemic lupus erythematosus who were followed at participating rheumatology units. A total of 359 variables including demographic data, clinical manifestations, disease activity, severity, comorbidities, LN outcome, treatments, and mortality were recorded. Only patients with a histological confirmation of LN were included. We performed a descriptive analysis, chi-square or Student's t tests according to the type of variable and its relationship with LN. Odds ratio and confidence intervals were calculated by using simple logistic regression. LN was histologically confirmed in 1092/3575 patients (30.5%). Most patients were female (85.7%), Caucasian (90.2%), and the mean age at LN diagnosis was 28.4 ± 12.7 years. The risk for LN development was higher in men (M/F:47.85/30.91%, P  < 0.001), in younger individuals ( P  < 0.001), and in Hispanics ( P  = 0.03). Complete response to treatment was achieved in 68.3% of patients; 10.35% developed ESRD, which required a kidney transplant in 45% of such cases. The older the patient, the greater was the likelihood of complete response ( P  < 0.001). Recurrences were associated with persistent lupus activity at the time of the last visit ( P  < 0.001) and with ESRD ( P  < 0.001). Thrombotic microangiopathy was a risk factor for ESRD ( P  = 0.04), as for the necessity of dialysis ( P  = 0.01) or renal transplantation ( P  = 0.03). LN itself was a poor prognostic risk factor of mortality (OR 2.4 [1.81–3.22], P  < 0.001). Patients receiving antimalarials had a significantly lower risk of developing LN ( P  < 0.001) and ESRD ( P  < 0.001), and responded better to specific treatments for LN ( P  = 0.014). More than two-thirds of the patients with LN from a wide European cohort achieved a complete response to treatment. The presence of positive anti-Sm antibodies was associated with a higher frequency of LN and a decreased rate of complete response to treatment. The use of antimalarials reduced both the risk of developing renal disease and its severity, and contributed to attaining a complete renal response. Abstract : Supplemental Digital Content is available in the text